Outcome of Posterior Cruciate Ligament Avulsion Fractures from Tibial Attachment Treated by Open Reduction and Internal Fixation - Khambalkar, Shouryashil V.; Patil, Tanish C.; Patil, Jaydeep K.; Ghorpade, Kapil R.; Naik, Nagesh (International Journal of Integrated Health Sciences, 2023)
Objectives: To analyze the clinical and functional outcomes of posterior cruciate ligament avulsion fractures treated by open reduction and internal fixation from tibial attachment.Methods: This observational study was conducted at the orthopedics department of a tertiary care medical college. Forty adult patients with PCL avulsion fractures were included in this study based on predefined inclusion and exclusion criteria. All patients were treated by open reduction and internal fixation. Patients were followed up for one year. The Lysholm scale and knee society score were used to assess functional outcomes. A p-value less than 0.05 was considered to be statistically significant.Results: Overall, 34 (75 %) males and 6 (15%) females participated in this study with an M: F ratio of 1:0.17. The mean age of affected patients was 37.3 +/- 7.34 years. Out of 40 patients, 29 (72.50%) patients sustained fractures secondary to road traffic accidents, while 7 (17.50%) had sports-related injuries. There was a highly significant improvement in the Lysholm and Knee Society scores from the time of presentation to the final follow-up (P<0.0001). Only 1 (2.5%) patient developed residual joint instability as evidenced by the drawer test result.Conclusion: Patients with posterior cruciate ligament avulsion fracture treated by Open reduction and internal fixation were found to have excellent results in terms of functional outcomes.